Hubungan Tingkat Pengetahuan Pasien dengan Tingkat Kecemasan Pasien Pre Operasi Katarak di Poli Mata RSUD Bendan Kota Pekalongan - Muhammad Fitriyanto; prastiwi, dani; Nonik Eka Martyastuti (LPPM UNIKAL, 2024)
Cataract is a clouding of the lens that can be seen from reduced visual acuity or reduced function felt by the patient. Most cataracts are treated with surgical procedures . Until now, no medicne, food and drink or sport activities have been found to prevent and treat patients with cataract vision problems. this type of research uses a cross sectional approach which aims to determine the relationship between knowledge and anxiety levels in pre-cataract surgery patients. This research was conducted at the ophthalmology clinic at Bendan Regional Hospital, Pekalongan City from 15 September to 31 October 2024 with a total sample size of 60 respondents. Sampling was taken by accidental sampling using a questionnaire. The results of statistical tests using the chi-square test obtained a p value <0.001, which means a p value <0.05. This could mean that there is a relationship between the level of patient knowledge and the level of anxiety of patients pre-cataract surgery at the eye clinic at Bendan Regional Hospital, Pekalongan City. In this study, the majority of respondents were > 60 years old, female, had a high school education, and the majority had received information about pre-cataract surgery through mass media or social media.